Managing Endothelial Dysfunction in COVID-19 - Matli, Kamal (2022)
Background Coronavirus disease 2019 (Covid-19) is associated with endothelial dysfunction. Pharmacologically targeting the different mechanisms of endothelial dysfunction may improve clinical outcomes and lead to reduced morbidity and mortality Methods In this pilot, double-blind, placebo-controlled, randomized clinical trial we assigned patients who were admitted to the hospital with mild, moderate, or severe COVID-19 infection to receive, on top of optimal medical therapy, either an endothelial protocol consisting of (Nicorandil, L-arginine, Folate, Nebivolol, and Atorvastatin) or placebo for up to 14 days. The primary outcome was time to recovery, measured by an 8 category ordinal scale and defined by the time to being discharged from the hospital or hospitalized for infection-control or other nonmedical reasons. Secondary outcomes included the composite outcome of ICU admission or the need for mechanical ventilation, all-cause mortality, and the occurrence of side effects Results Of 42 randomized patients, 37 were included in the primary analysis. The mean age of the patients was 57 years; the mean BMI of study participants was 29.14. History of hypertension was present in 27% of the patients, obesity in 45%, and Diabetes Mellitus in 21.6%. The median(Interquartile range) time to recovery was not significantly different between the endothelial protocol group (6 [4-12] days) and the placebo group (6 [5-8]days)(p-value = 0.854). Furthermore, there were no statistically significant differences in the need for mechanical ventilation or ICU admission, all-cause mortality, and the occurrence of side effects between the endothelial protocol group and the placebo group. Conclusion Among patients hospitalized with mild, moderate, or severe COVID-19 infection, targeting endothelial dysfunction by administering Nicorandil, L-arginine, Folate, Nebivolol, and Atorvastatin on top of optimal medical therapy did not decrease time to recovery. However, this treatment protocol was associated with an excellent safety profile. Adequately sized prospective randomized controlled trials are needed for the evaluation of the role of treating endothelial dysfunction in COVID-19 infection.